Promoting Students Reading Comprehension Through Systemic Functional Linguistics-Reading to Learn (SFL-R2L) - Izzah, Lidiyatul; Hadi, Muhamad Sofian; Dalai, Madeena; Walidy, Farhan (English Language in Focus (ELIF), 2024)
This study aims to investigate in detail the process and the result of improving English reading skills through Systemic Functional Linguistics-Reading to Learn (SFL-R2L). This study is an action research conducted in English Department Muhammadiyah University of Jakarta with total amount of participant 30 students within three action research cycles. The data was gathered from the process of observation in participation level and the result of an English reading skills test.  The findings showed that the learning process using Systemic Functional Linguistics-Reading to Learn (SFL-R2L) attracted the students to be more active in their learning process, it is showed by their participation level in the learning interaction. The result also presented that students’ English reading skill were a significantly improved. It can be concluded that the use of Systemic Functional Linguistics-Reading to Learn (SFL-R2L) succeeded in improving student English reading skills.